An Empirical Study on the Determinants of Bank Financial Stability: The Moderating Role of Bank Size in the Relationship Between Financial Performance - Fitrianingsih Fitrianingsih (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to measure the determinants of bank financial stability in Indonesia, with a focus on the effect of financial performance measured using the Z-Score ratio as a proxy for financial stability, Return on Assets (ROA) as a proxy for profitability, Capital Adequacy Ratio (CAR) for liquidity, and Loan to Deposit Ratio (LDR) as a proxy for solvency, along with the natural logarithm of total assets to measure the moderating variable of Bank Size. The sample was selected using purposive sampling from the population of banking companies listed on the Indonesia Stock Exchange (IDX) that fall under the KBMI 4, 3, and 2 bank categories in 2025, with time series data from 2020 to 2024. The analysis was conducted using the Moderated Regression Analysis (MRA) method. The results of this study show that CAR has a significant effect on bank financial stability from 2020 to 2024, and that Bank Size significantly moderates the effect of LDR. The findings are expected to provide valuable insights for regulators, bank management, and investors in maintaining and enhancing the stability of the financial system in Indonesia. The results of this study show that between Return on Asset (ROA), Loan to deposit Ratio (LDR) and Capital Adequacy Ratio (CAR), CAR has a significant effect on bank financial stability during the period 2020–2024, and that the Bank Size variable is able to significantly moderate the effect of the LDR variable. The implication of this research is that bank management must have regulations are designed to be able to minimize risks and avoid defaults so that the profitability of banks increases in Indonesia